2016
DOI: 10.1007/s10661-016-5739-8
|View full text |Cite
|
Sign up to set email alerts
|

Lead isotope ratios in lichen samples evaluated by ICP-ToF-MS to assess possible atmospheric pollution sources in Havana, Cuba

Abstract: Epiphytic lichens, collected from 119 sampling sites grown over "Roistonea Royal Palm" trees, were used to assess the spatial distribution pattern of lead (Pb) and identify possible pollution sources in Havana (Cuba). Lead concentrations in lichens and topsoils were determined by flame atomic absorption spectrophotometry and inductively coupled plasma (ICP) atomic emission spectrometry, respectively, while Pb in crude oils and gasoline samples were measured by ICP-time of flight mass spectrometry (ICP-ToF-MS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Nevertheless, the reported isotope ratio precision of Sr is comparable to the previously reported precision of Cu and Ag isotopes measured by second generation ICP-TOFMS. 27,33 In case of Pb, the isotope ratio precision reported here is better than reported in most previously studies using first and second generation ICP-TOFMS 24,27,39,42,59 except for one study using first generation ICP-TOFMS that reported comparable results 18 (see Table S1 in ESI†). A previous study using second generation ICP-TOFMS investigated the relationship between integration time and isotope ratio precision and showed that the isotope ratio precision can be as good as 0.02% when extended integration times of 100 s are used.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, the reported isotope ratio precision of Sr is comparable to the previously reported precision of Cu and Ag isotopes measured by second generation ICP-TOFMS. 27,33 In case of Pb, the isotope ratio precision reported here is better than reported in most previously studies using first and second generation ICP-TOFMS 24,27,39,42,59 except for one study using first generation ICP-TOFMS that reported comparable results 18 (see Table S1 in ESI†). A previous study using second generation ICP-TOFMS investigated the relationship between integration time and isotope ratio precision and showed that the isotope ratio precision can be as good as 0.02% when extended integration times of 100 s are used.…”
Section: Resultscontrasting
confidence: 58%
“…, 205 Tl/ 203 Tl for Pb. 35,39 This IIF correction factor f is subsequently applied to the isotopic system of interest assuming a constant IIF for both elements. 37 The internal inter-elemental IIF correction model can correct for mass dependent IIF but not for any mass independent IIF.…”
Section: Introductionmentioning
confidence: 99%
“…The highest value of EFZn=61.6 was determined at station 24 as expected due to his high Zn concentration at this station close to the former car bodyshop, punchbowls and constructions. In Cuba, leaded fuels are not used since the end of the 90s (Montero et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Further, to the authors' knowledge, this is the first application of the unique full-spectra capabilities single particle ICP-TOF-MS analysis to detect and characterize NP in plant tissues. Older generations of ICP-TOF-MS technologies (without single particle capabilities) have been used to quantify co-occurrence of analytes in samples, including plant tissue-based samples [75][76][77], and this type of analysis is extended here. While ICP-TOF-MS was useful for the evaluation of the method, the lack of association of plant material with the NP indicates that TOF-MS is not essential to characterize the single-metal NP types tested here.…”
Section: Resultsmentioning
confidence: 99%